2х(х-3)-3х(х+5) (А+7)(А-1)+(А-3) в квадрате 3(у+5) в квадрате -3ув квадрате PLEASE РЕШИТЕ...

0 голосов
59 просмотров

2х(х-3)-3х(х+5)

(А+7)(А-1)+(А-3) в квадрате

3(у+5) в квадрате -3ув квадрате

PLEASE РЕШИТЕ СРОЧНО НАДО!!!


Алгебра (57 баллов) | 59 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

2х(х-3)-3х(х+5)=2х^2-6x-3x^2-15x= -x^2-21x

 

(А+7)(А-1)+(А-3)^2=A^2+7A-A-7+A^2-6A+9=2A^2+2

 

3(у+5)^2-3у^2=3y^2+30y+75-3y^2=30y+75

(271k баллов)
0 голосов

2х(х-3)-3х(х+5)=2x^2-6x-3x^2-15x=-x^2-21x

 

(А+7)(А-1)+(А-3)^2=A^2-A+7A-7+A^2-6A+9=2A^2+2

 

3(у+5)^2-3у^2=3(y^2+10y+25)-3y^2=3y^2+30y+75-3y^2=30y+75

(10.3k баллов)